The Rosie project - Simsion, Graeme C. (New York : Simon & Schuster, 2014)
Don Tillman, a professor of genetics, sets up a project designed to find him the perfect wife, starting with a questionnaire that has to be adjusted a little as he goes along. Then he meets Rosie, who is everything he's not looking for in a wife, but she ends up his friend as he helps her try to find her biological father.
Target "Club Pick" on cover
Keywords: College teachers -- Australia -- Fiction; Genetics -- Research -- Fiction; Marriage -- Fiction; Love stories